Mapping Homicide Clusters across the United States Using County Level Data, 2004-2012 with Comparisons to Earlier Studies. Issue 2 (1st February 2021) - Amin, Raid; Yang, Hongbo; Lynch, Michael J.
ABSTRACT: Mapping crime can help identify geographic areas where crime clusters, and potentially help reveal factors that affect the production of crime at the structural level. Such information could have useful policy purposes. This study examines county-level homicide clusters in the US (2004–2012), and compares them to results from prior studies. The analysis employs SaTScan TM covariate adjustments based on epidemiological mapping algorithms used in disease surveillance. Though homicide rates in the USA have been decreasing long term, significant homicide clusters were identified for several geographic regions adjusting for median age, percent white, and percent living in poverty. Over time, homicide clusters remain somewhat stable, but change in terms of geographic scope. We also compare our maps to those derived by Baller et al.to show changes in homicide clusters in the US since 1960.